2020
DOI: 10.1111/cob.12398
|View full text |Cite
|
Sign up to set email alerts
|

“I am the embodiment of an anorexic patient's worst fear”: Severe obesity and binge eating disorder on a restrictive eating disorder ward

Abstract: Summary Adolescents who have been diagnosed with an eating disorder commonly have comorbid mental health conditions which have a significant impact on illness trajectory and may even limit access to effective treatment. Current models of eating disorder care focus mainly on treatment for patients diagnosed with restrictive eating disorders with fewer options available for those with binge eating disorder. We describe a case of an adolescent living with severe, complex obesity and binge eating disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Considering binge eating is part of BN’s diagnostic criteria, 6 it is particularly surprising to see the lack of binge eating discussion among the #miarecovery videos. This likely aligns with how treatment centers tend to emphasize disrupting restrictive behaviors and place a smaller focus on disrupting binge eating behaviors outside of BED specific treatment [ 64 ]. Furthermore, it may align with an avoidance of discussing binge eating due to the shame associated with it [ 65 ].…”
Section: Discussionmentioning
confidence: 69%
“…Considering binge eating is part of BN’s diagnostic criteria, 6 it is particularly surprising to see the lack of binge eating discussion among the #miarecovery videos. This likely aligns with how treatment centers tend to emphasize disrupting restrictive behaviors and place a smaller focus on disrupting binge eating behaviors outside of BED specific treatment [ 64 ]. Furthermore, it may align with an avoidance of discussing binge eating due to the shame associated with it [ 65 ].…”
Section: Discussionmentioning
confidence: 69%
“…However, there is a lack of appropriate care options for youth with disordered eating disorder and/or severe obesity, which highlights possible inequities in care. 35 Given the increasing prevalence of obesity and mental illness in adolescents, it is critical to create the evidence needed to support these treatment models of care for youth.…”
Section: Discussionmentioning
confidence: 99%
“…The BETR program is designed to specifically serve the needs of patients struggling with BESD. A case report suggested that having patients with BESD participate in treatment programs designed primarily for restrictive eating disorders may be problematic due to differing foci of weight restoration versus normalizing eating patterns, as well as patients’ comparisons to other patients, which can be detrimental to recovery [ 24 , 25 ]. Although there is little empirical evidence to support this, a study of intensive treatment specifically for patients reporting episodes of overeating (patients with BN, BED, or obesity without binge eating) found improvements in eating disorder psychopathology after 5 weeks, suggesting that targeted specialty care may be more effective and more efficient than general eating disorder treatment programs that address a wide range of symptomatology [ 26 ].…”
Section: Methodsmentioning
confidence: 99%